Dampak Study Ekskursi Dalam Meningkatkan Soft Skill Pada Mahasiswa Prodi Manajemen - Allen A. Ch. Manongko (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2021)
College students need to master adequate soft skills as a preparation for entering the world of work or the world of business. This study aims to determine what soft skills are important to be mastered by students and to find out how their coaching strategies are. This qualitative research fulfills the literature study procedure. The results of the study of 106 article documents resulted in an overview of the basic soft skills that students need to master, namely communication, leadership and teamwork, as well as supporting soft skills such as critical thinking, responsibility, work ethics, interpersonal, collaboration, problem solving and self-confidence. The strategy of developing student soft skills needs to be carried out in an integrated manner guided by the institutional vision and mission between curricular activities, co-curricular activities, and extracurricular activities which are strengthened by stimulation to organize events and are supported by community formation and application of student code of ethics and rules policies and back-up with an information system web-based student organization activities. In anticipation of faster changes, the soft skills needed to face the industrial revolution 4.0 still need attention. Likewise, soft skills related to religious values must also be developed to maintain the existence of future generations from the onslaught of value changes as a result of the industrial revolution 4.0. The results of the study skill and knowledge of student have growth until 20% with among of faster changes, and the soft skills needed to face the industrial after past.